The digital facilitator: A multivariate analysis of predictors of academic cheating - Enokela, Abel Ebiega; Alordiah, Caroline Ochuko; Aluede, Oyaziwo Omon (Journal of Interdisciplinary Studies in Education, 2026)
The pervasive issue of academic dishonesty in higher education is exacerbated by evolving digital technologies. This study empirically investigates the relative and hierarchical predictive power of institutional, personal, social, and digital factors on the frequency of cheating behavior among university students. A cross-sectional survey design was employed with a sample of 1,120 students. Data were analyzed using bivariate correlations and a five-step hierarchical regression analysis. Rigorous diagnostic checks were conducted to validate the model. Bivariate correlations revealed significant relationships between all the predictors and cheating, with the digital factor showing the strongest association (r = .570). The final regression model explained 41.2% of the variance in cheating behavior.